2015
DOI: 10.1002/ijc.29501
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic rewiring of pancreatic ductal adenocarcinoma: New routes to follow within the maze

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a debilitating and almost universally fatal malignancy. Despite advances in understanding of the oncogenetics of the disease, very few clinical benefits have been shown. One of the main characteristics of PDAC is the tumor architecture where tumor cells are surrounded by a firm desmoplasia. By reducing vascularization, thus both oxygen and nutrients delivery to the tumor, this stroma causes the appearance of hypoxic zones driving metabolic adaptation in surviving tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 94 publications
(199 reference statements)
2
28
0
Order By: Relevance
“…It has been reported that the one-carbon metabolism and proline metabolism pathways interconnect with glycolysis and pentose phosphate pathway to provide ATP, and NADH and NADPH (mediators of electron transfer for energy, reductive biosynthesis and redox defense) [8, 9, 42]. (Pink indicates upregulated pathways in MSKCC subset; grey indicates other heterogeneous pathways).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the one-carbon metabolism and proline metabolism pathways interconnect with glycolysis and pentose phosphate pathway to provide ATP, and NADH and NADPH (mediators of electron transfer for energy, reductive biosynthesis and redox defense) [8, 9, 42]. (Pink indicates upregulated pathways in MSKCC subset; grey indicates other heterogeneous pathways).…”
Section: Discussionmentioning
confidence: 99%
“…The cycling of proline catabolism and proline synthesis acts as a redox shuttle between the mitochondria and cytosol to maintain redox homeostasis [41, 42]. Furthermore, increased proline biosynthesis contributes to cancer cell growth by providing NAD+/NADP+ molecules to the pentose phosphate pathway and to glycolysis [40].…”
Section: Discussionmentioning
confidence: 99%
“…The drivers of PDAC metabolic preference are likely reflective of both oncogenic signaling pathways and the unique desmoplastic stromal microenvironment [13, 18–20]. It has been proposed that poor vascularization and hypoxia contribute to metabolic features of PDAC, while others have recently demonstrated that stromal diversity (activated vs .…”
Section: Introductionmentioning
confidence: 99%
“…This may indicate that when cancer has already developed, amino acid exhaustion results in the reduction of these amino acids. Glucose and glutamine metabolism is one of the most disturbed pathways in PC and has been intensively investigated for its potential therapeutic value [7, 19, 20]. Glutamine-dependent metabolism is critical for PC cell growth [21].…”
Section: Discussionmentioning
confidence: 99%